Exploring Challenges in Maternal and Child Health Services through Qualitative Analysis: Mengeksplorasi Tantangan dalam Layanan Kesehatan Ibu dan Anak melalui Analisis Kualitatif - Lailul Mursyidah; Lailatul Khilmi (Academia Open, 2024)
This study investigates the quality of Maternal and Child Health (MCH) services at Prambon Health Center in Sidoarjo Regency and identifies inhibiting factors. Using qualitative methods, data was gathered through interviews, observation, and documentation. Findings reveal satisfactory levels of responsiveness, guarantees, and empathy, but deficiencies in reliability and physical evidence due to incomplete ultrasound equipment and a shortage of health workers. Addressing these issues is crucial for enhancing MCH service quality and improving health outcomes in the community. Highlight: Reliability Shortcomings: Health worker reliability affects patient appointment fulfillment. Incomplete Equipment: Lack of complete ultrasound equipment hampers service provision. Addressing Shortages: Resolving workforce and equipment deficiencies crucial for service enhancement Keyword: MCH services, Prambon Health Center, service quality, inhibiting factors, qualitative study